2002
DOI: 10.4037/ajcc2002.11.6.567
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 0.12% Chlorhexidine Gluconate Oral Rinse in Reducing Prevalence of Nosocomial Pneumonia in Patients Undergoing Heart Surgery

Abstract: • Background Decreasing the levels of bacteria in the oropharynx should reduce the prevalence of nosocomial pneumonia. • Objectives To test the effectiveness of 0.12% chlorhexidine gluconate oral rinse in decreasing microbial colonization of the respiratory tract and nosocomial pneumonia in patients undergoing open heart surgery. • Methods A prospective, randomized, case-controlled clinical trial design was used. Peridex (0.12% chlorhexidine gluconate) was the experimental drug, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(112 citation statements)
references
References 7 publications
0
109
0
3
Order By: Relevance
“…The use of chlorhexidine particularly in instances where toothbrushing is not possible has been recommended by Ransier et al (1995). The potential role of chlorhexidine to prevent VAP in mechanically ventilated patients has also been evaluated and the effectiveness of this anti-plaque agent in reducing VAP incidence was apparent (Houston et al, 2002;Koeman et al, 2006;Chlebicki and Safdar, 2007;Tantipong et al, 2008;Özçaka et al, 2012). More interestingly, while the use of chlorhexidine in otherwise healthy gingivitis patients is considered adjunctive to mechanical plaque control methods, its use in intubated patients, on the other hand, has been shown to be more important and superior than toothbrushing in decreasing the risk of VAP (Munro et al, 2009;Scannapieco and Binkley, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The use of chlorhexidine particularly in instances where toothbrushing is not possible has been recommended by Ransier et al (1995). The potential role of chlorhexidine to prevent VAP in mechanically ventilated patients has also been evaluated and the effectiveness of this anti-plaque agent in reducing VAP incidence was apparent (Houston et al, 2002;Koeman et al, 2006;Chlebicki and Safdar, 2007;Tantipong et al, 2008;Özçaka et al, 2012). More interestingly, while the use of chlorhexidine in otherwise healthy gingivitis patients is considered adjunctive to mechanical plaque control methods, its use in intubated patients, on the other hand, has been shown to be more important and superior than toothbrushing in decreasing the risk of VAP (Munro et al, 2009;Scannapieco and Binkley, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…169 Optimizing oral health with chlorhexidine mouthwashes twice daily was shown in 2 studies to reduce respiratory infection and nosocomial pneumonia in patients undergoing heart surgery. 170,171 While studies evaluating use of chlorhexidine in general ICU populations have shown little outcome effect, 2 studies in which chlorhexidine oral care was included in bundled interventions showed significant reductions in nosocomial respiratory infections. 172,173 Other steps to decrease aspiration risk would include reducing the level of sedation/analgesia when possible, minimizing transport out of the ICU for diagnostic tests and procedures, and moving the patient to a unit with a lower patient:nurse ratio.…”
Section: D3 Use Of Enteral Feeding Protocols Increases the Overall Pmentioning
confidence: 99%
“…17 The frequency of the intervention was based on the result of four randomized controlled trials regarding the effects of oral care using chlorhexidine in an ICU. [18][19][20][21] Interventions were provided at 5 am and 5 pm each day by research assistants according to the research protocol.…”
Section: The Interventionmentioning
confidence: 99%